2010
DOI: 10.1021/jp106523b
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinium Formate Decomposition on the (101) TiO2-Anatase Surface: Combined Minimum Energy Reaction Pathway Calculations and Temperature-Programmed Decomposition Experiments

Abstract: Local minima, saddle points, and connecting intrinsic reaction paths for the decomposition of guanidinium formate (GuFo) on a (101) TiO2-anatase surface and in the gas phase have been studied on the basis of density functional theory (DFT) energy surfaces. We are aware of only one preceding electronic structure theory study of reaction barriers at a slab surface model. The formation of ammonia and carbon dioxide as final products of the GuFo decomposition is proposed to proceed in three principal stages: first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…1 . Bernhard et al (2012) and Todorova et al (2010) showed that ammonia could also be formed by the hydrolysis of urea in the presence of TiO 2 . The ammonia concentrations (and, therefore, the urea concentrations) were obtained at room temperature with help of a calibration model, using a UV–Visible spectrophotometer (Model Lambda 35, manufactured by Perkin Elmer) in the wavelength range of 570 to 720 nm.…”
Section: Methodsmentioning
confidence: 99%
“…1 . Bernhard et al (2012) and Todorova et al (2010) showed that ammonia could also be formed by the hydrolysis of urea in the presence of TiO 2 . The ammonia concentrations (and, therefore, the urea concentrations) were obtained at room temperature with help of a calibration model, using a UV–Visible spectrophotometer (Model Lambda 35, manufactured by Perkin Elmer) in the wavelength range of 570 to 720 nm.…”
Section: Methodsmentioning
confidence: 99%
“…According to the optimized geometries of the adsorbed intermediate species, reactant and product, the tentative geometry of transition state was prepared by gradually adjusting the cluster structures along the minimum energy path on the PES [35]. The initial guess structure is crucial to making the subsequent optimization of transition states be successfully converged.…”
Section: Methods and Theorymentioning
confidence: 99%
“…Only recently, we have reported about catalytic urea thermolysis (1) under steady state conditions over different metal oxides. 26 Also, a theoretical study of Todorova et al (2011) proposes catalytic urea thermolysis. These authors calculated the reaction energy barriers for the hydrolysis of guanidine on anatase TiO 2 (101) using density functional theory (DFT) and found adsorbed urea as an intermediate on the TiO 2 surface.…”
Section: Introductionmentioning
confidence: 99%
“…These authors calculated the reaction energy barriers for the hydrolysis of guanidine on anatase TiO 2 (101) using density functional theory (DFT) and found adsorbed urea as an intermediate on the TiO 2 surface. 27 From the adsorbed urea NH 3 can be eliminated, leaving HNCO on the catalyst surface. HNCO then hydrolyzes via carbamic acid as another intermediate.…”
Section: Introductionmentioning
confidence: 99%